Simultaneous study of matrix metalloproteinases, proinflammatory cytokines, and soluble cytokine receptors in the tears of noninfectious corneal ulcer patients - Sakimoto, Tohru; Ohnishi, Takako; Ishimori, Akiko (Graefe's archive for clinical and experimental ophthalmology, 2014)
Background We investigated the presence of matrix metalloproteinases (MMPs), tissue inhibitors of metalloproteinases (TIMPs), proinflammatory cytokines, and soluble cytokine receptors in the tear fluid of patients with noninfectious corneal ulcers in the peripheral cornea. Methods The subjects were 20 eyes of 17 patients with peripheral noninfectious corneal ulcers and 20 eyes of 20 volunteers. Tear samples were taken by the Schirmer test I method and the presence of MMPs (MMP-1, MMP-2, MMP-3, MMP-8, MMP-9, MMP-10, and MMP-13) and TIMPs (TIMP-1, TIMP-2, and TIMP-4) were investigated using an MMP antibody array system. The concentrations of proinflammatory cytokines {IL-1β, IL-6, and TNF-α (tumor necrosis factor-alpha)} and soluble cytokine receptors {soluble (s) IL-1R1, sIL-1R2, sIL-2Rα, sIL-4R, sIL-6R, sTNFR1, sTNFR2, s-vascular endothelial growth factor receptor (VEGFR) 1, sVEGFR2, sVEGFR3, and sgp130} were determined using the multiplex bead immunoassay system. Results The concentrations of MMP-8 and MMP-9 were significantly up-regulated in the tear fluid of the ulcer patients, whereas TIMPs concentrations did not change. The concentrations of IL-1β, IL-6, sIL-1R2, sIL-6R, sTNFR1, and sTNFR2 were up-regulated in the ulcer patients, whereas sgp130 and sVEGFR1 concentrations significantly decreased. Conclusions The presence of some MMPs increased significantly in the patients with peripheral noninfectious corneal ulcers, whereas the presence of TIMPs remained unchanged. Although some proinflammatory cytokines were up-regulated, their antagonists, soluble cytokine receptors, were also up-regulated. It is thus possible that the up-regulation of MMPs disrupts the balance between the MMPs and TIMPs and that this balance may play a pivotal role in the pathophysiology of corneal ulceration.